PENGARUH KECANDUAN GAME ONLINE DAN MOTIFASI BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA DI KELAS XI SMK NEGERI 5 MANADO - Manongko, Allen; Lempas, Jety; Mamentu, Meike; Rori, Hizkia (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of Online Game Addiction and Learning Motivation on Student Learning Outcomes at SMK Negeri 5 Manado. The research method used is a quantitative method with a sample of 56 students selected randomly. Data collection techniques were carried out through questionnaires and documentation. The data obtained were then analyzed using multiple linear regression analysis methods, simple correlation analysis, and multiple correlation analysis. The results of the study indicate that: (1) There is a significant effect between Online Game Addiction and Student Learning Outcomes, with a tcount value > ttable (12.752 > 2.004); (2) There is a significant effect between Learning Motivation and Student Learning Outcomes, with a tcount value > ttable (6.389 > 2.004); and (3) Simultaneously, Online Game Addiction and Learning Motivation have a significant effect on Student Learning Outcomes of 74.53%, with a fcount value > ftable (29.395 > 3.171). This study concludes that learning technology and learning motivation have a role in improving student learning outcomes. Keywords: Online Game Addiction, Learning Motivation, Learning Outcomes, SMK Negeri 5 Manado